P83 Intravenous drug use: not a barrier to achieving a sustained virological. (16th November 2010) - Dillon, J; Jafferbhoy, H; Miller, M; Tait, J; Cleary, S
Abstract : Introduction: Chronic hepatitis C (CHC) is a leading cause of liver disease with a variable rate of progression to decompensated cirrhosis, hepatocellular carcinoma and death. It is a common infection among intravenous drug users (IDU). It can be cured by combination therapy of Pegylated interferon and Ribavarin. IDU patients are under represented in many treatment cohorts, this has been justified on grounds of safety and the fear that lowered treatment success would reduce the cost effectiveness of therapy. Aim: To ascertain in routine clinical practice the outcomes of treating individuals with HCV who are active IDU or are on substitution therapy such as methadone. The primary outcome measure was the rate of sustained virological response (SVR) in those from an IDU background compared to those infected by other aetiologies. Method: The HCV treatment database was retrospectively analysed for consecutively treated patients. The patients treated were divided in three groups based on the risk category for acquisition of Hepatitis C. Primary end point was SVR which was calculated on intention to treat basis in these groups. Similarly patients were not excluded because of co-infection with HBV and HIV or comorbidity such as haemophilia and chronic renal failure. Results: We assessed treatment outcome in 291 consecutively treated, predominately treatment naive patients who received Peg interferon and Ribavarin for HCV. They were predominately male (70.3%) in the economically productive age group with 10% of the patients having cirrhosis. Major genotype was three accounting for 53.9% followed by G1 at 36.7%. The overall SVR rate was 55.3%. The SVR rates achieved were; Non IDU 61.4%, Ex IDU 54.8%, and Active IDU 47.1% (p=n/s). In each of the three groups G1 patients obtained an SVR of ; Non IDU 52.7%, Ex IDU 30.7% and active IDU 35.4% (p=n/s). In the non G1 patients non IDU 65.1%, Ex IDU 76.7% and active IDU 53.5%. Ex IDU had a significantly better SVR than active IDU (p=0.02), other differences not significant. Conclusion: Our results demonstrate that with simple support SVR rates in the active drug user group can be achieved which are comparable with non IDU infected individuals. Intravenous drug use should not be seen as a barrier to treatment of individuals with HCV.